Language learning strategies of students at different levels of speaking proficiency - Cabaysa, Carissa C. (2008)
This study aimed to investigate the language learning strategies employed by high school students and to determine the effects of these on their speaking abilities. Observation of English, mathematics, and science classes, interviews focused on observed behavior, analyses of classroom interaction transcripts and retrospection statements yielded quantitative and qualitative data. Checklist results also served as bases for comparing strategy use of the novice and intermediate speakers, using the one-way anova or f-test while the significance of differences in the strategies of the two groups was analyzed using the chi-square. Results revealed that the subjects used strategies in the following order: metacognitive, social-affective, and compensation strategies. The students' employment of differeent learning strategies could further contribute to improving their speaking abilities if they would gain knowledge about learning strategies, and consequently help them develop autonomy in learning English.